Persepsi Wisatawan Cruise Viking Orion Terhadap Kualitas Produk Paket Wisata Halfday Nature, Tradition & Religion Tour di PT. Destination Asia - Ni Kadek Maharani Artha; Ni Putu Evi Wijayanti; I Gede Ngurah Primanda S Rahadiarta (J-TRUE: Journal of Travel and Leisure, 2024)
Since long time ago cruise tourists have a great opportunity for travel agencies in Bali. One of the Travel Bureaus that has been operating since 2002, PT Destination Asia, is eyeing the cruise tourist market. Starting from selling services and services to selling tour package products, in this case one of the tour packages that attracts attention is the Halfday Nature, Tradition & Religion Tour package product which is very often sold to cruise tourists on Viking Orion ships where this ship is the first to often use services and also buy tour package products at PT. Destination Asia. In selling quality tour package products requires things that must be considered, namely Core Product, Tangible Product and Augmented Product. The data obtained from this research are observation, interviews, questionnaires and literature studies. The data analysis techniques used are validity tests, reliability tests and descriptive statistics. The results of the research obtained are tourist perceptions of Core Product with an average of 4.53 which shows very good results, tourist perceptions of Tangible Product with an average of 4.56 which shows very good results and tourist perceptions of the augmented product dimension which is 4.57 with very good results, but what is very unfortunate is that the core product cannot pass the value of the average product.